Inovação social no modelo de associações de pacientes com doenças raras através do Design Estratégico - Bittencourt, Gustavo Berwanger (Universidade do Vale do Rio dos Sinos, 2020)
This research investigates the contribution of Strategic Design to the community of people with rare diseases, a social group historically marked both by the most diverse and acute socioeconomic difficulties and by a willingness to organize themselves which presents, according to Barbosa and Portugal (2018), limitations concerning their autonomy. In this context, this work aims to understand which processes Strategic Design can promote to stimulate social innovation in the current model of rare disease patients' organizations. To address this problem, its main objective is to propose principles for these projects. As specific objectives, it seeks to establish connections between Strategic Design, Social Innovation and the context of the associations, in addition to mapping and formulating Strategic Design processes that can collaborate in this endeavor. This is done mainly, studying authors who research or have researched Strategic Design and Social Innovation intersection, such as Ezio Manzini, Anna Meroni, François Jégou, Karine Freire, Carlo Franzato, Ione Bentz and Gustavo Borba, among others. The research analyzes through Ginburg’s Evidential Paradigm (1989), as proposed by Braga (2008), a codesign process formulated and applied to a group of people involved with Prader-Willi Syndrome in the city of Porto Alegre, based on guidelines of Strategic Design, Community Centered Design and Management by Mandalas. Beyond results from the theoretical and practical reflection, we propose a tool for the development of associative organizational models. The Strategic Social Innovation Matrix emerges in this work to respond to the need for a Strategic Design tool linked to the mentioned authors and focused on the characteristics of social groups with associative intentions, seeking a way to innovate in their organizational model as an alternative to the forms available, especially those with market logic.
Keywords: Design estratégico; Inovação social; Doenças raras; Associativismo; Strategic design; Social innovation; Rare diseases; Associativism; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial